Strawberries : Production, Postharvest Management and Protection - Sharma, R. M. (Radha Mohan); Yamdagni, Rakesh; Dubey, Anil Kumar; Pandey, Vikramaditya (Boca Raton, FL : CRC Press, 2019)
This book provides unparalleled integration of fundamentals and most advanced management to make this strawberry crop highly remunerative besides enhancing per capita availability of fruit even in the non-traditional regions of the world.
Chapter 18 PollinationChapter 19 Fruit Development; Chapter 20 Use of Plant Bio-regulators; Chapter 21 Special Cultural Practices; Chapter 22 Protected Cultivation; Chapter 23 Soilless Culture; Chapter 24 Harvesting; Chapter 25 Yield and Varietal Performance; Chapter 26 Post-Harvest Handling and Storage; Chapter 27 Value Addition; Chapter 28 Physiological Disorders; Chapter 29 Integrated Disease Management; Chapter 30 Integrated Insect Pest Management; Chapter 31 Pesticide Residues; Chapter 32 Production Economics and Marketing; Chapter 33 Challenges, Potential and Future Strategies; Index
OCLC-licensed vendor bibliographic record.
Keywords: Strawberries; SCIENCE -- Life Sciences -- Botany; TECHNOLOGY -- Agriculture -- General; TECHNOLOGY -- Food Science